Clinical evaluation of percutaneous kyphoplasty in the treatment of osteolytic and osteoblastic metastatic vertebral lesions. (June 2016) - Wang, Yimeng; Liu, Hao; Pi, Bin; Yang, Huilin; Qian, Zhonglai; Zhu, Xiaoyu
Abstract: Percutaneous vertebral augmentation (Percutaneous vertebroplasty, PVP and Percutaeous kyphoplasty, PKP) for the treatment of metastatic spinal lesions has been considered as a preferred alternative to relieve pain and rebuild spinal stabilization relying on minimally invasive procedure. However, there have been few reports on clinical outcomes of percutaneous kyphoplasty in the treatment of osteolytic and osteoblastic metastatic vertebral fracture. We report our experience for 81 kyphoplasty procedures performed in 45 patients with thoracic and lumbar vertebral lesions caused by metastases. 4 out of the 45 patients were withdrawn at 1-year follow-up. 41 patients demonstrated good clinical result. The osteoblastic group performed a better pain relief in visual analog scale (VAS) score after the treatment than the osteoclastic group 3 days, 1 month, 3 months and 1 year after the KP. And the Oswestry Disability Index (ODI) scores of the osteoblastic group is lower than that of the osteoclastic group just in 3 days after the KP. And there were no significant difference between the two groups of ODI scores 1 month, 3 month and 1 year after the KP. And there were no statistical differences of the radiographic parameters including VB height variation and local kyphosis angle (LKA) between the two groups. Kyphoplasty results in an effective, minimally invasive procedure for the stabilization of thoracic and lumbar metastatic vertebral lesions, including both osteoblastic and osteoclastic types, which achieves statistically significant pain relief, function improvement, preventing further local kyphotic deformity, and VB height. Highlights: Kyphoplasty, a minimally invasive procedure. Clinical outcomes of kyphoplasty in the treatment of osteolytic and osteoblastic metastatic vertebral fracture. Retrospective study reveals that kyphoplasty achieves statistically significant pain relief, function improvement, and preventing further local kyphotic deformity for treating osteoblastic and osteoclastic metastatic spinal lesions.